Structure and function of adhesion GPCRs and their ligands - Araç, Demet (Henry Stewart Talks, 2019)
The history, biological functions and architecture of adhesion GPCRs, The conserved GAIN domain, Working models for adhesion GPCR activation, The structures of adhesion GPCR extracellular regions and their ligands, Similarity of adhesion GPCRs to hormone receptors, Drugs might affect adhesion GPCRs via the extracellular regions or protein-protein interaction sites